RNAi living-cell microarrays for loss-of-function screens in Drosophila melanogaster cells. - Wheeler, D.B.; Bailey, S.N.; Guertin, D.A.; Carpenter, A.E.; Higgins, C.O.; Sabatini, D.M. (Nature Methods, 2004)
RNA interference (RNAi)-mediated loss-of-function screening in Drosophila melanogaster tissue culture cells is a powerful method for identifying the genes underlying cell biological functions and for annotating the fly genome. Here we describe the development of living-cell microarrays for screening large collections of RNAi-inducing double-stranded RNAs (dsRNAs) in Drosophila cells. The features of the microarrays consist of clusters of cells 200 mum in diameter, each with an RNAi-mediated depletion of a specific gene product. Because of the small size of the features, thousands of distinct dsRNAs can be screened on a single chip. The microarrays are suitable for quantitative and high-content cellular phenotyping and, in combination screens, for the identification of genetic suppressors, enhancers and synthetic lethal interactions. We used a prototype cell microarray with 384 different dsRNAs to identify previously unknown genes that affect cell proliferation and morphology, and, in a combination screen, that regulate dAkt/dPKB phosphorylation in the absence of dPTEN expression.